Insight Into Function and Subcellular Localization of Plasmopara viticola Putative RxLR Effectors - Chen, Tingting; Liu, Ruiqi; Dou, Mengru; Li, Mengyuan; Li, Meijie; Yin, Xiao; Liu, Guo-tian; Wang, Yuejin; Xu, Yan (Frontiers in Microbiology, 2020)
Grapevine downy mildew, caused by oomycete fungus Plasmopara viticola, is one of the most devastating diseases of grapes across the major production regions of the world. Although many putative effector molecules have been identified from this pathogen, the functions of the majority of these are still unknown. In this study, we analyzed the potential function of 26 P. viticola effectors from the highly virulent strain YL. Using transient expression in leaf cells of the tobacco Nicotiana benthamiana, we found that the majority of the effectors could suppress cell death triggered by BAX and INF1, while seven could induce cell death. The subcellular localization of effectors in N. benthamiana was consistent with their localization in cells of Vitis vinifera. Those effectors that localized to the nucleus (17/26) showed a variety of subnuclear localization. Ten of the effectors localized predominantly to the nucleolus, whereas the remaining seven localized to nucleoplasm. Interestingly, five of the effectors were strongly related in sequence and showed identical subcellular localization, but had different functions in N. benthamiana leaves and expression patterns in grapevine in response to P. viticola. This study highlights the potential functional diversity of P. viticola effectors.